Mathematics as a Male Domain: A Study of Perception in Costa Rican Secondary Education - Meza-Cascante, Luis Gerardo (2021)
Introduction. The results of a study on the perception of mathematics as a male domain in official day high school students in Costa Rica are presented. The study was conducted to evaluate the need to develop intervention programs that promote that women have the same capabilities as men in mathematics. “Male domain” is understood as the belief that men have better conditions than women to learn mathematics and, in general, to perform in environments related to that discipline. Method. This descriptive quantitative research studies the variable by sex, educational level, or school location area, applying the scale Mathematics as a male domain by Fennema and Sherman (1976). The sample consisted of 3,581 students in 2018 (50.8% female), selected by simple cluster sampling. In the data analysis, the statistical techniques of Student’s t and Welch (complemented with the Scheffé test) were used. Results. Differences were found between men and women, with men showing higher levels in the variable, with a moderate effect size. Differences were detected between the seventh and eighth level students with those of the ninth, tenth and eleventh levels, with higher values for the first two levels. Differences were also found between schools located in urban areas and those in rural areas, showing higher levels of perception of mathematics as a male domain in the latter, with a moderate effect size. Discussion. The research reveals that approximately 84% of the students have low to very low levels of perception of mathematics as male dominance, which is seen as a positive finding. The results suggest the convenience of developing intervention programs that promote that women have the same competencies as men in mathematics.